STUDY OF THE INFLUENCE OF ISLAMIC FINANCIAL LITERACY AND TRUST ON SAVING INTEREST WITH DEMOGRAPHICS AS A MEDIATOR - Irdiana, Sukma; Kusnanto Darmawan; Ninik Lukiana (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2025)
The purpose of this study was to examine the influence of Islamic financial literacy and trust on savings interest, with demographics as a mediator. A descriptive quantitative approach was used, involving a population of active students in Lumajang Regency, with a sample size of 170 selected through purposive sampling. Path analysis was employed as the technique. The findings show that Islamic financial literacy directly affects demographics, while trust does not. Islamic financial literacy does not influence savings interest, but trust and demographics do. Indirectly, Islamic financial literacy impacts savings interest through demographics, while trust does not.